Expression Signature of lncRNAs and mRNAs in Sevoflurane-Induced Mouse Brain Injury: Implication of Involvement of Wide Molecular Networks and Pathways - Congshan Jiang (International Journal of Molecular Sciences, 2021)
Sevoflurane, one of the most commonly used pediatric anesthetics, was found to cause developmental neurotoxicity. To understand specific risk groups and develop countermeasures, a better understanding of its mechanisms is needed. We hypothesize that, as in many other brain degeneration pathways, long non-coding RNAs (lncRNAs) are involved in the sevoflurane-induced neurotoxicity. Postnatal day 7 (PD7) mice were exposed to 3% sevoflurane for 6 h. To quantify neurotoxicity in these mice, we (1) detected neural apoptosis through analysis of caspase 3 expression level and activity and (2) assessed long-term learning ability via the Morris water maze at PD60. To elucidate specific mechanisms, profiles of 27,427 lncRNAs and 18,855 messenger RNAs (mRNAs) in mouse hippocampi were analyzed using microarray assays. Sevoflurane-induced abnormal lncRNA and mRNA expression-associated function pathways were predicted by bioinformatic analysis. We found that sevoflurane induced significant neurotoxicity, causing acute neuroapoptosis and abnormal expression of 148 mRNAs and 301 lncRNAs on PD7 in mouse hippocampus. Additionally, exposed mice exhibited impaired memory on PD60. Bioinformatic analysis predicted that the dysregulated mRNAs, which are highly correlated with their co-expressed dysregulated lncRNAs, might be involved in 34 neurodegenerative signaling pathways (e.g., brain cell apoptosis and intellectual developmental disorder). Our study reveals for the first time that neonatal exposure to 3% sevoflurane induces abnormal lncRNA and mRNA expression profiles. These dysregulated lncRNAs/mRNAs form wide molecular networks that might contribute to various functional neurological disease pathways in the hippocampus, resulting in the observed acute apoptosis and impaired long-term memory.